Longitudinal Study of the Vascular Glycocalyx and Urinary Podocyte Markers During Pregnancy - Garcia Valencia, Oscar; Suvakov, Sonja; Tu, Haitao; Dilmaghani, Darah; Milic, Natasa M.; Weissgerber, Tracey L.; Dokic, Vladimir; Gavrilovici, Paul; Hatamova, Jennet; Miao, Jing; White, Wendy M.; Jayachandran, Muthuvel; et al. (Journal of the American Heart Association, 2025)
We aimed to assess the longitudinal changes of glycocalyx, a proteoglycan/glycoprotein layer that lines and protects endothelial cells in normotensive pregnancies (NPs); to correlate glycocalyx parameters with kidney injury markers (podocin-positive to nephrin-positive [P/N] ratio); and to explore changes in P/N ratio in preeclampsia. Plasma and urine samples and glycocalyx measurements using side-stream darkfield imaging were collected at each trimester from pregnant women (n=31). Plasma glycocalyx components were measured by ELISA, and urinary P/N-positive extracellular vesicles by flow cytometry. In NPs (n=26), glycocalyx degradation increased from the first to the second trimester ( =0.008) and returned to first-trimester values in the third trimester ( =0.008). Microvascular perfusion decreased from the first to the second trimester ( =0.006) and increased back to first-trimester values by the third trimester ( =0.039). Plasma syndecan 1 level showed a steady increase from the first to the second trimester ( <0.001) and further in the third trimester ( <0.001); hyaluronic acid increased from the first to the second trimester ( =0.016) without further changes. Glycocalyx degradation was associated with an increase in P/N ratio from the first to the second trimester of NPs and remained stable through the third trimester. P/N ratio strongly correlated with elevated syndecan 1 and hyaluronic acid levels in the third trimester. Comparison of P/N ratios between NP and preeclampsia (n=5) showed higher values in preeclampsia across all trimesters ( =0.028). Glycocalyx changes during NPs are associated with elevated urinary podocyte markers. Increase in P/N ratio across NPs, and further in preeclampsia, suggests that podocyte injury in preeclampsia is extension of physiological changes in pregnancy, which may predate its clinical presentation.